Pengaruh Stres Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Departemen Kinitting PT Kahatex - Anglaeni, Leni; Sarah, Siti (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze the influence of work stress and work discipline on employee performance in the Knitting Department of PT Kahatex, Cimahi, West Java. This research uses a quantitative method with an associative approach. Data collection techniques include pre-surveys, questionnaires, interviews, and document collection, with a population of 65 individuals (respondents) used as the sample. Data analysis includes validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, t-tests, and f-tests. The results show that work stress has a significant negative effect on employee performance by 34.2%. From the partial hypothesis testing, the value of t-count > t-table (4.876 > 2.000) was obtained, indicating that H0 is rejected and H1 is accepted, meaning there is a significant negative influence of work stress on employee performance in the Knitting Department of PT Kahatex. Work discipline has a significant positive effect on employee performance by 57.8%. From the partial hypothesis testing, the value of t-count > t-table (7.953 > 2.000) was obtained, indicating that H0 is rejected and H2 is accepted, meaning there is a significant positive influence of work discipline on employee performance. Based on the simultaneous hypothesis testing, work stress and work discipline together have a significant positive effect on employee performance, with a determination coefficient of 68.5%. The remaining 31.5% is influenced by other factors not examined in this study. The simultaneous hypothesis testing shows that the value of F-count > F-table (28.532 > 3.150), indicating that H0 is rejected and H3 is accepted, meaning there is a significant positive simultaneous influence of work stress and work discipline on employee performance in the Knitting Department of PT Kahatex, Cimahi, West Java.